Targeting the development of soft skills in developing countries: Evidence from a growing literature - Leight, Jessica (Inter-American Development Bank, 2021)
More and more researchers and policymakers are interested in whether and how a broad array of skills, often summarized as non-cognitive skills, soft skills, life skills, or socioemotional skills, may benefit individuals in educational settings or in the labor market. A large literature in the U.S. and other industrialized countries has identified high returns to non-cognitive skills in the labor market, suggesting that individuals who can successfully develop attributes such as patience, self-control, extraversion, or high aspirations, can benefit from a meaningfully different economic trajectory (Heckman & Kautz, 2012). At the same time, this has raised the question of whether non-cognitive skills are malleable, and subject to development through targeted programs that seek to develop individuals’ competencies along these dimensions.